Experience of COVID 19 disease on 159 Ecuadorian chronic dialysis patients - Santacruz, Juan C. (2020)
Aim: In December 2019, first Covid-19 disease cases were reported. The pandemic spread with 42,039,763 cases and 1,141,223 deaths worldwide with 156,451 confirmed cases and 12,500 deaths in Ecuador. The aim of this work is to share characteristics and clinical outcomes of 159 dialysis patients in Quito during pandemic. Materials and methods: Observational-prospective-unicenter study. Fifty-six consecutive patients (35%) presented COVID19 symptoms and followed since April to 30 September 2020. Positive nasopharyngeal PCR testing confirmed diagnosis. Low oxygen saturation (LOS) classified disease as severe, moderate if symptoms without LOS and asymptomatic if no symptoms. Hospital-stay, time disease, mortality, contagious rate data were collected. Results: Thirty-seven patients (23.3%) tested positive. Patients with LOS at presentation and hospitalized were older when compared with those without LOS (61.6 ± 11.9 vs 48.9 ± 11.9 years; p=0.02) and non-hospitalized (60.3 ± 12.7 vs 51.4 ± 15.6 years; p=0.02). Ten died (27%), mortality was significative in patients with previous pulmonary disease (p=0.01), LOS (p=0.03), hospitalization (p=0.01), and severe disease (p=0.03). Median hospital stay was 7 days (3-13), time disease was 17 days (6-25) and 10 days (6-22) until death. Conclusion: COVID-19 disease has increased mortality and health care demand in dialysis patients. Mortality was inferior to other series, and significative when previous pulmonary pathology, low oxygen saturation, hospitalization and severe disease were present.